Komunikasi Spiritual dalam Upaya Mengatasi Masalah Generasi Muda dengan Metode Self Healing - I Dewa Bagus Caka Putra (Program Studi Magister S2 Ilmu Komunikasi Hindu Institut Agama Hindu Negeri Gde Pudja Mataram, 2021)
This paper aims to introduce a communication model that can be applied as an approach to solve the spiritual problems of the younger generation, especially for students who are members of the spiritual group “Family Lightworker 11:11”. The model is called therapeutic spiritual communication. As we know that parents or lecturers often faced with problems that are carried out by the younger generation. One of the problems that rarely gets attention is related to the spiritual problems experienced by the younger generation. With different characters, spiritual problems require their own approach in handling them. The type of this research is qualitative with the Self Healing method and uses a descriptive analysis approach. The result of this research showed that spiritual communication with the Self Healing method can be used as a therapeutic method to solve the spiritual problems of the younger generation. By using the steps and principles of the therapeutic communication such as problem assessment, problem diagnosis, therapeutic action plan, and therapeutic action spiritual communication can be designed as an approach to solving the spiritual problems of the younger generation. The spiritual intelligence that is achieved through spiritual communication, meditation, and understanding their psychology will have an impact on changing the way of life of the younger generation, their attitude and behavior towards others, and the quality of work and learning they participate in.